Sustainable Entrepreneurial Intention: The Perceived of Triple Bottom Line among Female Students - Kartika Nuringsih, Nuryasman MN, IwanPrasodjo, Rita Amelinda (Jurnal Manajemen, 2019)
The purpose of the study is to investigate the factors associated with the sustainable entrepreneurial intention on undergraduate students. In line with the sustainable development program, it observes the intention which is perceived by female students. Based on previous of studies, four variables are determined, consisting of role models, entrepreneurship education, entrepreneurial support, and green value. The female students of an economics faculty from one of the entrepreneurial universities in Jakarta were selected as the sample for the study. By using multiple regression, determinants of student intention was computed. Results are shown as follows: the perceived green value is able to predict the intention. Inversely, perceived role models, entrepreneurship education, and entrepreneurial support are insignificant. Understanding their perceptions within the concept of sustainable entrepreneurship is an important stage when designing the mechanism of triple bottom line implementation in the high education level, specifically in developing the entrepreneurial education.